(untitled) (Al Insyirah International Scientific Conference on Health, 2023)
In 2017, Indonesia had a maternal death rate of 305 per 100,000 live births. In 2017, the MMR in Kampar District was 73 per 100,000 live births, compared to 112 per 100,000 live births in Riau Province. The mother and fetus will suffer if the initial stage of labor lasts too long. This study was conducted at Bangkinang Hospital in the Kampar Regency to ascertain the impact of the mother’s position on the duration of labor during the first active phase. This kind of study uses a post-test only control group and a true experiment research design in a quantitative manner. Between April and July 2019, the study was conducted at the Bangkinang Hospital. Mothers who gave birth between April to June 2019 at the Bangkinang Hospital made up the study’s sample, which included 16 respondents standing and 16 respondents in an oblique maternity position. Purposive sampling was used as the sample technique. The dependent T test was used for computerized univariate and bivariate data analysis. The majority of respondents to this study experienced the first active phase of the rapid phase up to 56.3% of the time, and there was a relationship between the mother’s position and the length of the active phase of the first stage of labor at Bangkinang Hospital in Kampar Regency (p = 0.003), according to the study’s findings. It is suggested that both parties consider using the standing maternity position as a backup option to quicken labor.